The complete chloroplast genome sequence of Quercus ningangensis and its phylogenetic implication - Tian-Rui Wang; Zheng-Wei Wang; Yi-Gang Song; Gregor Kozlowski (Plant and Fungal Systematics, 2021)
Quercus ningangensis is an economically and ecologically important tree species belonging to the family Fagaceae. In this study, the complete chloroplast (cp) genome of Q. ningangensis was sequenced and assembled, and 18 published cp genomes of Quercus were retrieved for genomic analyses (including sequence divergence, repeat elements, and structure) and phylogenetic inference. With this study, we found that complete cp genomes in Quercus are conserved, and we discovered a codon composition bias, which may be related to genomic content and genetic characteristics. In addition, we detected considerable structural variations in the expansion and contraction of inverted repeat regions. Six regions with relatively high variable ( matK-rps16 , psbC , ycf3 intron, rbcL , petA-psbJ , and ycf1 ) were detected by conducting a sliding window analysis, which has a high potential for developing effective genetic markers. Phylogenetic analysis based on Bayesian inference and maximum likelihood methods resulted in a robust phylogenetic tree of Quercus with high resolution for nearly all identified nodes. The phylogenetic relationships showed that the phylogenetic position of Q. ningangensis was located between Q. sichourensis and Q. acuta . The results of this study contribute to future research into the phylogenetic evolution of Quercus section Cyclobalanopsis ( Fagaceae ).